Propagação vegetativa e anatomia da madeira de espécies reófitas para utilização em recuperação de matas ciliares - Raddatz, Dione Dambros (2019)
Natural resources, especially the forest formations have been destroyed through the disordered occupation and without planning of the Brazilian territory, the removal of these formations causes several problems to the environment, mainly collaborating with the extinction of species of flora and fauna, climatic changes, soil erosion and silting of watercourses. The vegetation set that inhabits rivers and streams are called riparian forest, and has several tree species and shrub species, many of them popularly known as ''sarandis''. These sites, once degraded, require different forms of recovery, and for that, you must know in advance the area of the watershed, the pluviometric regime, as well as the area where they will be deployed recovery practices and methods for introduction of species. In this way, different tools are needed to recover them, because where periodic flooding occurs the vegetative propagation by means of cuttings is the most indicated. The present study aims to investigate the vegetative propagation by cuttings and the flexibility of stems of species Aspidosperma riedelii Müll. Arg., Callisthene inundata O.L.Bueno, A.D.Nilson & R.G.Magalh., Calyptranthes concinna DC., Colliguaja brasiliensis Klotzsch ex Baill., Erythroxylum substriatum O.E.Schulz, Indigofera suffruticosa Mill., Lafoensia nummularifolia A. St.-Hil., Lafoensia pacari A. St.-Hil., Ludwigia sericea (Cambess.) Hara e Maytenus sp. for use in the recovery of degraded areas in the river. The experiment of vegetative propagation by cuttings was carried out in a greenhouse, the cuttings of the ten species had 15 cm long and were planted in 1.7 L pots using medium sieved sand as the substrate. The completely randomized design was chosen with 30 cuttings for each species. At 45, 90 and 180 days, survival rate was evaluated and of the aerial part: the mean number, mean length and dry mass of shoots per cutting. For the root system: the mean number, mean length and dry mass of tap roots per cutting, the number of roots, and sum of root length per meter of buried cutting, and for a better understanding of the root system was held, at 180 days, the absolute distribution of roots. The anatomical studies were carried out for species not yet described anatomically, from samples collected at the diameter at breast height, of the plants where the cuttings were originated, in order to describe preliminarily the composition of the wood, emphasing characters that confer flexibility on the stems and branches. Microscopic descriptions followed the recommendations of the IAWA Committee. In the results, the vegetative propagation species showed a mean survival rate ranging from 51% to 96%, all ten had an aerial system, however only the species C. concinna, C. brasiliensis, I. suffruticosa, L. pacari and L. sericea presented root system. In the anatomical analysis of the wood, it was identified that A. riedelii, L. nummularifolia and L. pacari have technical features that confer flexibility on the stem and branches, however, it does not discard the species E. substriatum and Maytenus sp, because in addition to being found in a rheophile environment they have very narrow vessels and thin- walled, since these technical features are constantly found in reophyte species.